2019
DOI: 10.22158/wjssr.v6n1p45
|View full text |Cite
|
Sign up to set email alerts
|

Negative Affect, Life Satisfaction, and Internet Gaming Disorder: Exploring the Mediating Effect of Coping and the Moderating Effect of Passion

Abstract: <em>No research has examined whether the effect of high negative affect and poor life satisfaction on Internet Gaming Disorder (IGD) is explained by gaming to cope or is dependent upon users’ passion for video gaming. An online sample of adults (N = 969 adults; 60.5% male) reported their passion for video games, positive and negative affect, life satisfaction, and IGD severity. A latent profile analysis on the passion subscales yielded four subgroups: (1) minimally passionate; (2) moderately passionate; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 56 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…Overall, the problematic online gaming might be defined as a complex psychological health condition which involves a feature of everyday life activities with potential negative outcomes. Indeed, although online gaming might offer an alternative context in which individuals can experiment personal social competences, reducing stress, problems, and isolation through online social interactions [16][17][18][19]30], it might concurrently limit social experiences in face-to-face contexts when the online life starts to overshadow the offline one [23,80,94,106]. Consequently, following the theoretical work of Caplan [7], some gamers might find refuge in online games with decreasing depressive symptoms, social anxiety, and loneliness, whereas, in other gamers' experiences, these correlates might increase, ensuring online socialization but failing in providing the needed face-to-face interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the problematic online gaming might be defined as a complex psychological health condition which involves a feature of everyday life activities with potential negative outcomes. Indeed, although online gaming might offer an alternative context in which individuals can experiment personal social competences, reducing stress, problems, and isolation through online social interactions [16][17][18][19]30], it might concurrently limit social experiences in face-to-face contexts when the online life starts to overshadow the offline one [23,80,94,106]. Consequently, following the theoretical work of Caplan [7], some gamers might find refuge in online games with decreasing depressive symptoms, social anxiety, and loneliness, whereas, in other gamers' experiences, these correlates might increase, ensuring online socialization but failing in providing the needed face-to-face interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Among the Internet-related activities, specific structural characteristics of gaming (such as design and narrative, achievements, online social interactions, and motivations) appeared particularly fascinating for individuals who attempt to escape the boredom of common life [15]. Indeed, videogames seem to help individuals to escape real life and reduce stress, problems, and isolation also through online social interactions [16][17][18][19]. In this regard, according to the compensatory Internet use model [20••], online videogames might offer other alternative virtual environments where highly socially anxious individuals transfer most of their social activities (such as the formation of strong friendships), alleviate their stressful life event-related negative feelings, and feel safer and more comfortable than in face-to-face socialization [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there are a wide variety of variables that can be measured to establish links between IGD and impairment/distress, such as need satisfaction (Allen & Anderson, 2018), life satisfaction (Mills et al, 2019), externalising problems and more. In the secondary data used in this paper, no fewer than 21 different aspects of well-being were measured across the various studies, which can make straightforward comparison challenging.…”
Section: Flexibility In the Assessment Of Igd And Distressmentioning
confidence: 99%
“…The I-PANAS-SF is designed to be suitable for use with competent but not necessarily native English speakers and excludes redundant and ambiguous items [13]. The I-PANAS-SF has also been widely used in previous studies and has demonstrated good validity and reliability [13][14][15][16][17]. However, Karim and colleagues found only partial factorial invariance of the I-PANAS-SF among French and Pakistani university students for four items ("active," "afraid," "nervous," and "upset") [18].…”
Section: Introductionmentioning
confidence: 99%